2008
DOI: 10.1158/0008-5472.can-07-6590
|View full text |Cite
|
Sign up to set email alerts
|

WL-276, an Antagonist against Bcl-2 Proteins, Overcomes Drug Resistance and Suppresses Prostate Tumor Growth

Abstract: Patients with hormone-refractory prostate cancer (HRPC) have an estimated median survival of only 10 months because of acquired drug resistance, urging the need to develop therapies against the drug-resistant HRPC phenotype. Accumulating evidence suggests that overexpressing antiapoptotic Bcl-2 family proteins is at least partially responsible for the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Therefore, the VEGF–Bcl-2–CXCL8 pathway suggests new targets for the development of anti-angiogenic strategies. And nowadays, short interfering RNA and small molecule inhibitors of Bcl-2 are being developed to inhibit solid tumors (4648). In our present investigation, we demonstrated that treatment of (−)-gossypol led to obvious downregulation of VEGF in both cancer cells and endothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the VEGF–Bcl-2–CXCL8 pathway suggests new targets for the development of anti-angiogenic strategies. And nowadays, short interfering RNA and small molecule inhibitors of Bcl-2 are being developed to inhibit solid tumors (4648). In our present investigation, we demonstrated that treatment of (−)-gossypol led to obvious downregulation of VEGF in both cancer cells and endothelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The compound has gone through several clinical II studies for the treatment of patients with solid tumors and hematopoietic malignancies ( Shoemaker et al, 2006 ). On the other hand, optimization of BH3I-1 led to the discovery of WL-276 ( 11 in Figure 7 ) ( Wang et al, 2008 ) with a similar inhibitory activity against Bcl-2 and enhanced inhibitory activity against Bcl-X L as compared with gossypol. In contrast, WL-276 effectively induces apoptosis in PC-3 cells at low micromolar concentrations.…”
Section: The Bh3-bcl-2 Interactionmentioning
confidence: 99%
“…Isolation of the fragmented DNA is then done using such common methods for genomic DNA isolation as phenol-chloroform [15,41,43,44], or phenol-chloroform-isoamyl alcohol extraction [45]. A number of isolation procedures based on various physical and chemical principles are used for isolating apoptotic low molecular weight DNA fragments from apoptotic cells [46][47][48][49][50][51][52]. Commercial kits for this purpose mostly use solid-phase extraction on, for example, silica gel or glass fiber fleece.…”
Section: Dna Ladder Assaymentioning
confidence: 99%